Pengembangan Usaha Kelompok IRT Ceriping Singkong di Desa Suro melalui Intervensi TTG Berbasis Digital Economy di Desa Suro, Kecamatan Kalibagor, Banyumas - Wati, Ratna Kartika; Saputra, Eqwar; Alfalisyado (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2024)
Mitra is a group of IRT Cassava Chips. According to the results of observations and interviews with the head of the IRT Cassava Chips group, Mrs. Fajar Apriana, said that the cassava chips made by this home business are still not good in appearance or taste, especially since the packaging is still simple. The shape of the cassava chips is not yet homogeneous, they are still big, small and thick and thin because they still use a manual slicing tool. Initially in Suro Village there were around 18 home industries that made cassava chips, but because the products were not selling well on the market, many of them went out of business and turned to farm laborers. The average production of this home industry is around 10 kg/day. They leave them in stalls and some sell them directly to the market. Even though the business has been around for a long time, it has not been able to develop optimally, the cassava chip production activity has not been able to meet all consumer demand. This is because the equipment is still manual, resulting in soreness, fatigue and less ergonomic posture of workers. The aim of this activity is a) to help the Suro Village Cassava Chips Housewife Group get the right and legal capital free from loan sharks b) to create a comfortable environment for workers so that it affects their work productivity and c) helps improve their products, their marketing strategies are appropriate and digitally based, they are also halal certified or PIRT certified. IbM outputs are scientific articles that will be published in National Journals as mandatory outputs, articles published on social media , activity videos and Copyright as additional output.